Gifting the Ungifted: Disproportionality of Minority Students in Gifted Education - Catania, Nicholas (Journal of the American Academy of Special Education Professionals, 2018)
This paper centers on the topic of gifted education. Namely, the focus of the discussion will be on the underrepresentation of students of color in gifted education, the underachievement of students of color in gifted education, and proportionate and equitable representation in gifted education. This paper examines research in the field over the past twenty years to shed light on the limited presence of high achieving minority students in gifted education. It is imperative that teachers understand this disproportionality in order to overcome the discrimination of the minority population.